2020
DOI: 10.35741/issn.0258-2724.55.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Contact and Service Quality Components Impact on Tourist Satisfaction

Abstract: The purpose of this paper aims to identify the components of service quality at specific tourist destinations and the crucial relationship between cultural contact and service quality in the Mekong Delta Region, Vietnam. The paper shows the relationship of tourists’ satisfaction, loyalty, and cultural contact after using the tourism service in the Mekong Delta Region, Vietnam based on qualitative and quantitative research. Data were obtained from 350 tourists, who responded willingly to a questionnaire-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Such tourists will therefore be thrilled and delighted about having the new experience, and derive more joy from it, thereby enhancing their satisfaction. Moreover, previous findings confirmed the key influence of cultural contact on tourist satisfaction (Romao et al, 2015;Valle et al, 2001;Vu et al, 2020). Therefore, the authors are proposing H 8 as follows:…”
Section: Cultural Contactmentioning
confidence: 65%
See 2 more Smart Citations
“…Such tourists will therefore be thrilled and delighted about having the new experience, and derive more joy from it, thereby enhancing their satisfaction. Moreover, previous findings confirmed the key influence of cultural contact on tourist satisfaction (Romao et al, 2015;Valle et al, 2001;Vu et al, 2020). Therefore, the authors are proposing H 8 as follows:…”
Section: Cultural Contactmentioning
confidence: 65%
“…H 8 : Cultural contact positively impact on tourist satisfaction (+) It is possible that a higher level of cultural contact is associated with revisit intention (H. Chen & Rahman, 2018;Romao et al, 2015;Vu et al, 2020). When tourists recognize the attractiveness and the beauty of a new culture, they will exhibit an active interest in the activities the destination/ site has to offer, partake in more activities, and enjoy their time more (H. Chen & Rahman, 2018).…”
Section: Cultural Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…So, tourists would be excited and enchanted to have a new experience and arise more delight from it, thus increasing their satisfaction. Similarly, previous research investigations found that cultural contact significantly influences tourist satisfaction [78,79]. It is also promising that a greater level of cultural contact has a significant influence on the revisit intention of tourists [54,78,79].…”
Section: Hypothesis 5 (H5) Tourist Satisfaction Significantly Mediate...mentioning
confidence: 55%
“…Other important things that support the needs of visitors in the Bogor Botanical Gardens such as the existence of food/beverage sales, souvenirs, toilets, and mosques that are quite easily accessible to visitors become an important point in a tourist area. The feeling of satisfaction gained from the good management performance will have a positive impact, as stated by Vu et al (2020), that when visitors are comfortable with tourism services, they will express that the trip will create a strong bond between each individual and nature of certain cultural values. The importance of optimal environmental management has implications for the satisfaction of visitors who come to Bogor Botanical Gardens, under Truong et al (2018) statement that human resources involved in the management aspect are one of the points that determine the satisfaction of visitors after traveling to a tourist area.…”
Section: Discussionmentioning
confidence: 99%